2023
DOI: 10.1021/acs.inorgchem.2c04243
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Regulation toward Bi3+ Selective Occupation for Full-Spectrum White Light Emission

Abstract: An activator’s selective occupation of a host is of great significance for designing high-quality white light-emitting diode phosphors, while achieving a full-spectrum single-phase white light emission phosphor is challenging. In this study, a boron phosphate solid-solution Na2Y2(BO3)2–x (PO4) x O:0.005 Bi3+ (NYB2–x P x O:0.005 Bi3+) white phosphor was designed by selectively occupying Bi3+ activators in the mixed anionic groups. The substitutes of the anionic unit (BO3)3– by the (PO4)3– unit are supposed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…19 Similarly, Wu et al reported a Lu 3 Al 2 Ga 3 -O 12 :Tb 3+ ML material, where the electron transition of the Tb 3+ ion from 5 D 3 → 7 F 6-4 and 5 D 4 → 7 F 6-0 contributed two different emission bands respectively, and the ML color varied with the applied stress. 20 The aforementioned results suggest that effective realization of stress-sensitive color variations can be achieved by harnessing the diverse luminescence behaviors exhibited by activators under stress. Generally, the luminescence kinetics of activators in ML materials are significantly affected by changes in the local crystal field environment.…”
Section: Introductionmentioning
confidence: 99%
“…19 Similarly, Wu et al reported a Lu 3 Al 2 Ga 3 -O 12 :Tb 3+ ML material, where the electron transition of the Tb 3+ ion from 5 D 3 → 7 F 6-4 and 5 D 4 → 7 F 6-0 contributed two different emission bands respectively, and the ML color varied with the applied stress. 20 The aforementioned results suggest that effective realization of stress-sensitive color variations can be achieved by harnessing the diverse luminescence behaviors exhibited by activators under stress. Generally, the luminescence kinetics of activators in ML materials are significantly affected by changes in the local crystal field environment.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanoluminescence (ML) is the mechanical-photon conversion process of a material under mechanical stimuli such as impact, torsion, stretching, and friction. [1][2][3][4][5][6] In 1605, Bacon first observed the ML phenomenon by scraping sugar. [7] In 1966, Butler discovered the deformation luminescence phenomenon of alkali metal halides.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to transition metal ions, the electron transition selection rules for lanthanide ion are also closely related to the corresponding site symmetry and crystal field intensity. [ 10 ] With changes in the local crystal environment, the emission spectral distribution may change differently. Thereinto, Pr 3+ is featured with a 4f 2 shell, and due to the 13 multiplets in the Pr 3+ 4f 2 configuration and non‐4f states, Pr 3+ exhibits varied luminescence behaviors in different host lattices.…”
Section: Introductionmentioning
confidence: 99%